Analisis Kebutuhan Fungsional Sistem Informasi Manajemen Gudang dengan Metode Pieces (Studi Kasus CV Karya Bangsa) - Turserno, Andi; Rosihan, Rifda Ilahy (Journal Industrial Manufacturing, 2022)
CV. Karya Bersama is a company engaged in the general equipment supplier. The problem of data processing, stock monitoring and reporting that occurs in warehouse operations at the company is still manual. As an effort to improve, the company is exploring the use of an information management system. The purpose of this study is to test the warehouse information management system that is being proposed based on the needs function using the PIECES (Performance, Information, Economy, Control, Efficiency Service) analysis method. The information system that has been generated in this design can manage incoming and outgoing goods data, control stock of goods, and can print stock reports, incoming goods reports, and outgoing goods reports. The results of the increase in efficiency in finding information on goods data are 74%, the efficiency increase for incoming goods data input is 77%, and the efficiency increase for outgoing goods input is 88%.Keywords: Information System, Warehouse, Design System, Inventory Management, PIECES Method.